The bride wore scarlet [large type] - Carlyle, Liz (Thorndike Press large print core series., 2011)
Anaïs de Rohan has faced danger in her past, but never anything so great as posing as the new bride to one of the St. James Society's most magnetic - and ruthless - leaders. But Lord Bessett's bold challenge that she prove herself worthy of joining his secret all-male society is impossible to resist. So she daringly agrees to travel with the enigmatic nobleman on a dangerous mission to save one of their own - a little girl with a frightening gift.